2016
DOI: 10.1186/s12906-016-1485-2
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects and related bioactive mechanism of Potentilla fruticosa L. leaves combined with Ginkgo biloba extracts studied with microbial test system (MTS)

Abstract: Background Potentilla fruticosa, also called “Jinlaomei” and “Gesanghua”, is widely used as folk herbs in traditional Tibetan medicine in China to treat inflammations, wounds, certain forms of cancer, diarrhoea, diabetes and other ailments. Previous research found P. fruticosa leaf extract (C-3) combined with Ginkgo biloba extracts (EGb) showed obvious synergistic effects in a variety of oxidation systems. The aim of the present study was to further confirm the synergy of P. fruticosa combined with EGb viewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
1
14
0
1
Order By: Relevance
“…The synergism between individual polyphenols or groups of these compounds may not only improve the properties of a singular raw material or extract but also positively affect the antioxidant activity of their various combinations. For example, the antioxidant activity of the leaves of Potentilla fruticosa, containing mainly hydrolysable tannins, was synergistically increased by the flavonoid fraction of Ginkgo biloba leaves [48].…”
Section: Interactions Of Model Polyphenols In the Frap Assaymentioning
confidence: 99%
“…The synergism between individual polyphenols or groups of these compounds may not only improve the properties of a singular raw material or extract but also positively affect the antioxidant activity of their various combinations. For example, the antioxidant activity of the leaves of Potentilla fruticosa, containing mainly hydrolysable tannins, was synergistically increased by the flavonoid fraction of Ginkgo biloba leaves [48].…”
Section: Interactions Of Model Polyphenols In the Frap Assaymentioning
confidence: 99%
“…The antimicrobial activity of D. fruticosa polar extracts against Gram-positive and Gram-negative bacteria, spore-forming bacteria, and fungi has been verified in some previous publications, indicating the potential use of these extracts as natural antimicrobial agents in various food systems [7,8,10,11]. A few years ago, Liu et al and Wang et al demonstrated that D. fruticosa leaf extracts when combined with green tea polyphenols or Ginkgo biloba extracts show synergistic, additive, and antagonistic effects on a variety of oxidation systems [12][13][14]. The reported bioactivity of these extracts is typically attributed to the high phenolic content of this plant.…”
Section: Introductionmentioning
confidence: 83%
“…In g urine samples are usually collected after establishing several time intervals for bette itoring of metabolite excretion. In the case of urine in human models, it is mostly co at the following intervals: (0-2), (2-5), (5)(6)(7)(8) and (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) h. In animal assays, they are u Urine samples are of special interest, since the excreted metabolites may be a reflection of the metabolic transformations produced in the original compounds of the extract. Regarding this type of sample, there are studies that use only a single interval of sample collection [59,60] and studies that use multiple collection intervals [58,61].…”
Section: Biological Samplesmentioning
confidence: 99%
“…Many of these studies have demonstrated the pleiotropic character of many bioactive compounds, which are capable of presenting beneficial effects on various therapeutic targets [7]. On the other hand, there are also in vitro studies that have attributed the bioactivity to a synergistic effect between several compounds; however, the mechanisms of action of these effects should be explored in greater depth [8,9]. Once the potential extracts are also chemically well characterized, these or the compounds that have shown beneficial effects are usually selected for further evaluation in animal models [10,11] and, finally, in clinical trials with humans [12,13].…”
Section: Introductionmentioning
confidence: 99%